Synthesis of flat-sheet thin film composite forward osmosis membranes - Wei, Jing (2013)
Forward osmosis (FO) is an emerging membrane separation technology. It is different from the well-studied pressure-driven membrane separation processes. The FO process is based on water transport under an osmotic pressure difference across a semi-permeable membrane. The distinct operating conditions lead to unique technical challenges during the exploitation of FO technology. According to a comprehensive literature investigation, one of the stringent barriers is lacking of effective FO membranes. The objectives of this research were to develop high performance FO membranes, and furthermore, to systematically study the mass transport and the governing mechanisms in FO process. Thin film composite (TFC) FO membranes with a tailored support structure were developed in this study. The membranes consisted of a highly porous substrate with finger-like pore structure, which was prepared via phase inversion, and a polyamide rejection layer synthesized by interfacial polymerization. The TFC FO membranes had small structural parameters due to the thin cross-section, low tortuosity, and high porosity of the substrates. The membrane rejection layers exhibited superior separation properties (higher water permeability and excellent selectivity) relative to commercial FO membranes. Under FO testing conditions, these membranes achieved high water flux while maintaining relatively low solute reverse diffusion. Comparison of the synthesized TFC FO membranes with commercial FO and reverse osmosis (RO) membranes revealed the critical importance of the substrate structure, with a straight finger-like pore structure preferred over a spongy pore structure to minimize internal concentration polarization (ICP), a unique and critical problem resulting in low water flux in the osmotically driven membrane processes. In addition, membranes with high water permeability and excellent selectivity are preferred to achieve both high FO water flux and low solute flux. The results proved that TFC membranes with a tailored porous substrate and rejection layer are promising for FO applications. In the study of polyamide rejection layer synthesis, the influence of monomer concentrations (i.e., m-phenylenediamine (MPD) and trimesoyl chloride (TMC) concentrations) on the membrane separation properties as well as the FO performance was systematically investigated. A strong trade-off between the water permeability and salt rejection of the membranes was observed, where reducing the MPD concentration or increasing the TMC concentration may result in a higher membrane permeability but a lower salt rejection. In FO tests, membranes with poor salt rejection had severe solute reverse diffusion, which enhanced the severity of ICP. It was found that the FO water flux was governed by both the membrane water permeability and solute rejection. For a membrane with higher water permeability but lower solute rejection, the reduced membrane frictional resistance was compensated simultaneously by the more severe solute-reverse-diffusion-induced ICP. The net effect on the FO water flux depends on the competition of these two opposing mechanisms. Under conditions where solute reverse diffusion may cause severe ICP (e.g., high draw solution concentration and high water flux level), membranes need to be optimized to achieve a high salt rejection even if this is at the expense of lower water permeability. In view of the importance of the water permeability and salt permeability on FO performance, a systematic comparison study of prevailing semi-permeable FO membranes with nanofiltration (NF)-like and RO-like separation properties in terms of flux performance and fouling behavior was conducted. Due to the crucial influence of solute reverse diffusion on FO water flux, the high-rejection RO-like FO membranes generally performed better than the NF-like counterparts in sodium chloride based FO tests. On the other hand, the high permeability of NF-like FO membranes could achieve higher water flux, when proper draw solutes were used to minimize draw solute leakage. Fouling tests suggested that the NF-like TFC FO membranes tended to be more fouling resistant due to their relatively smooth membrane surface. This work further elucidated the major mechanisms that govern the FO performance. These mechanisms were summarized as a frictional resistance loss mechanism (MR), solute-reverse-diffusion-induced ICP (MICP-Js), concentration of feed solutes (concentrative ICP or MICP-feed in the active-layer-facing-draw-solution orientation) and dilution of draw solutes (dilutive ICP or MICP-draw in the active-layer-facing-feed-solution orientation). These mechanisms are related to the properties of membrane, draw and feed solutions. This work led to a set of systematic criteria for the selection of FO membranes, draw solution and optimization of other operating conditions, of which the practicability was demonstrated in potential FO applications.